The Promotion of Climate-Smart Villages to Support Community-Based Adaptation Programming in Myanmar - Barbon, Wilson John; Vidallo, Rene R.; Gonsalves, Julian Francis (2017)
This report presents the highlights of a scoping study conducted by the International Institute of Rural Reconstruction (IIRR) in Myanmar. The study was funded by CCAFS in support of a plan to test and develop climate-smart villages in Myanmar. In 2015, through the initiative of CCAFS and after consultations with various agencies, the Myanmar Ministry of Agriculture and Irrigation adopted the Myanmar Climate-Smart Agriculture Strategy (MCSAS). This document lays out climate change impacts to agriculture in the country in broad terms, as well as the vision and goals of making agriculture in Myanmar climate-smart.